Phytochromes A and B Mediate Red-Light-Induced Positive Phototropism in Roots - Kiss, John Z. (American Society of Plant Biologists, 2003)
The interaction of tropisms is important in determining the final growth form of the plant body. In roots, gravitropism is the predominant tropistic response, but phototropism also plays a role in the oriented growth of roots in flowering plants. In blue or white light, roots exhibit negative phototropism that is mediated by the phototropin family of photoreceptors. In contrast, red light induces a positive phototropism in Arabidopsis roots. Because this red-light-induced response is weak relative to both gravitropism and negative phototropism, we used a novel device to study phototropism without the complications of a counteracting gravitational stimulus. This device is based on a computer-controlled system using real-time image analysis of root growth and a feedback-regulated rotatable stage. Our data show that this system is useful to study root phototropism in response to red light, because in wild-type roots, the maximal curvature detected with this apparatus is 30° to 40°, compared with 5° to 10° without the feedback system. In positive root phototropism, sensing of red light occurs in the root itself and is not dependent on shoot-derived signals resulting from light perception. Phytochrome (Phy)A and phyB were severely impaired in red-light-induced phototropism, whereas the phyD and phyE mutants were normal in this response. Thus, PHYA and PHYB play a key role in mediating red-light-dependent positive phototropism in roots. Although phytochrome has been shown to mediate phototropism in some lower plant groups, this is one of the few reports indicating a phytochrome-dependent phototropism in flowering plants.